Editorial - Kleiber, Michał; Burczyński, Tadeusz (Computer Assisted Methods in Engineering and Science, 2012)
We take pleasure in informing our readers that the journal “Computer Assisted Methods in Engineering and Science” (CAMES), a largely scope-expanded version of the previous 18-year old Polish Academy of Sciences journal (Computer Assisted Mechanics and Engineering Sciences) with the same acronym, starts from 2012 being published under the auspices of the European Community on Computational Methods in Applied Sciences – ECCOMAS (http://www.eccomas.org/). This is an important landmark in the evolution of CAMES. Its expanded scope will cover now all subjects traditionally addressed by ECCOMAS. Accordingly, the mission of CAMES aspires to promote research efforts of European universities, research institutes and industries active in the broader field of Mathematical Modeling and Computer Simulations in Engineering and Applied Sciences, including traditional areas of Solid and Structural Mechanics, Fluid Dynamics, Acoustics and Electromagnetics but going beyond them to account for application relevant issues in Physics, Chemistry, Biology and Mathematics, Scientific Computing, Large Scale Optimization, Intelligent Systems and Multi-physics problems – as well as demonstrations of their practical use in solving real life problems. We have no doubts that the new format of the Journal will lead to the strengthening of the visibility of ECCOMAS serving in this way our common goal of promoting novel developments in computational engineering & applied science. As it is now widely recognized this area of scientific inquiry has been in the last decades under intensive development worldwide greatly contributing to the progress in virtually all research areas.Therefore, an additional effort at the European level to promote it as a critical methodological challenge involving applied mathematics, information science and different core science and engineering disciplines is believed to still be very much in place. The first issue contains a letter from ECCOMAS President Professor Manolis Papadrakakis and a seminal paper by Professor Erwin Stein, devoted to a comprehensive historical overview of the evolution of variational foundations for the broadly understood field of Computational Mechanics.